The relationship between professional quality of life and sleep quality among nurses working in intensive care units: a cross-sectional study - Parisa Mansouri; Mozhgan Rivaz; Razie Soltani; Parsa Tabei (BMC Nursing)
Abstract Background Intensive care unit (ICU) nurses work under heavy workloads, which can lead to serious consequences for nurses’ outcomes and patient safety. This study aimed to examine the relationship between professional quality of life (Pro QOL), and sleep quality among ICU nurses during the COVID-19 outbreak. Methods A cross-sectional and multicentre study was conducted on 253 nurses in 20 COVID-19 ICUs in four major teaching hospitals from July 2021 to June 2022. Data were collected via a demographic information form, the Professional Quality of Life Scale, and the Pittsburgh Sleep Quality Index (PSQI). Results Nurses in COVID-19 ICUs experienced moderate levels of compassion satisfaction, compassion fatigue, and poor sleep quality. The mean scores of the Pro QOL dimensions were 33.49 ± 6.77, 32.28 ± 8.83, and 29.58 ± 11.67 for compassion satisfaction, burnout, and secondary traumatic stress, respectively. The results revealed that 220 (87%) of the nurses experienced poor sleep quality. A significant relationship was shown between the Pro QOL dimensions and the mean total score of sleep quality, which can predict 0.45% of the variance (F = 7.11, p < 0.001, adjusted R2 = 0.45). Conclusion Our results confirmed the link between the Pro QOL and sleep quality among ICU nurses. It is suggested that nurse managers implement practical interventions to improve the QWL of nurses in the ICUS. This will subsequently lead to improved outcomes for nurses and ensure patient safety.